Culture of everyday life: to the issue of structure and content logic of the educational discipline. Part II - Нападиста, Валентина Григорівна (Київський національний університет імені Тараса Шевченка, 2021)
The article discusses the logic of structure and content of the discipline "Culture of Everyday Life", due to the complexity and versatility of the everyday life phenomenon and interdisciplinarity of methodological optics of its research, the variety of theoretical tools, which, in turn, determines the ambiguity of views on the very essence of the everyday life phenomenon and its components. The analysis of educational programs on "Culture of Everyday Life", that are placed among the elements of educational professional and scientific training programs on "Culture Studies" in higher education institutions in Ukraine, demonstrated the wide variability of their content and structure. In the second part of the article, the characteristic features of the everyday life and its oppositional worlds, which helps to delineate the boundaries of the everyday life, as well as its structures and factual and semantic content, are analysed. In particular, the human body and body techniques in the context of everyday practices; house and settlement as an organized and ordered space of everyday life; meals in different modes of gastronomic practices; clothing and its socio-stratification role in everyday life; emotional, regulatory and value foundations of the world of relationships in a family circle. The variability of the semantic content of the "culture of everyday life" concept is considered and the presence of problems in its conceptualization is noted. Based on this, the very name of the discipline "Culture of Everyday Life" is problematized. Emphasis is placed on the appropriateness of its replacement by "Culture Studies on Everyday Life", which would open new opportunities in the structural and thematic content of this discipline and would contribute to the formation of its own specifics in presenting the everyday life phenomenon, focused not on the boundless world of factuality or as a certain normativeness of everyday life, but on a conceptual view of its content and essence, the search for certain patterns in long-term historical durations, the change of which causes profound structural changes in human community as a whole.

Розглянуто логіку структурування та змістового наповнення навчальної дисципліни "Культура повсякденності", спричинена як складністю та багатогранністю самого феномену повсякденності, так і міждисциплінарністю методологічних оптик її дослідження, різноманітністю використовуваного теоретичного інструментарію, що, у свою чергу, обумовлює розмаїття поглядів на саму сутність феномену повсякденності та її складові. У другій частині статті предметом розгляду стали характерні ознаки повсякденного та його опозиційні світи, що допомагає окреслити межі світу повсякденного, а також структури повсякденності та їх фактологічно-смислове наповнення. Зокрема, тіло людини та техніки тіла в контексті повсякденних практик; дім та поселення як організований та впорядкований простір плину повсякденного життя; харчування у різних режимах гастрономічних практик; одяг та його соціально-стратифікаційна роль у повсякденні; емоційні, нормативно-регламентуючі та ціннісні підвалини світу взаємин у родинному колі. Проблематизується сама назва навчальної дисципліни "Культура повсякденності". Акцентується увага на доречності її заміни на "Культурологію повсякденності".
Культура повсякденності: до проблеми логіки структури та змісту навчальної дисципліни. Частина ІІ
Keywords: культура повсякденності; структура навчальної дисципліни; зміст навчальної дисципліни; структури повсякденності; культурологія повсякденності; the culture of everyday life; the discipline structure; the discipline content; everyday life structures; culture studies on everyday life